Meteorological data from Degerö (C18) - Svartberget Research Station (Swedish University of Agricultural Sciences, 2025)
Automatic weather station data from locations within the distributed Swedish research infrastructure SITES. Check preview or file for the specific parameters included at this location. Data has been quality controlled and cleaned from outliers and other events producing unrealistic data. Gaps have not been filled.
Svartberget Research Station (2025). Meteorological data from Degerö (C18), 2001–2014 [Data set]. Swedish Infrastructure for Ecosystem Science (SITES). https://hdl.handle.net/11676.1/_mzV3qJbg4LKLlGbx6_VAIou
Keywords: Svartberget Research Station; Atmospheric radiation; Humidity; Precipitation; Surface Winds; Time instant; Time instant; Air temperature; Air temperature; Snow depth; Snow depth; Net radiation; Net radiation; Air pressure; Air pressure; Incoming shortwave radiation; Incoming shortwave radiation; Relative humidity; Relative humidity; Soil temperature; Soil temperature; Wind direction; Wind direction; Wind speed; Wind speed; Soil Science; Markvetenskap; Agriculture, Forestry and Fisheries; Jordbruk, skogsbruk och fiske; Agricultural Science; Jordbruksvetenskap; Ecology; Ekologi; Multidisciplinary Geosciences; Multidisciplinär geovetenskap; Environmental Sciences; Miljövetenskap; Climate Science; Klimatvetenskap